PEMBERDAYAAN DAN PEMBELAJARAN PAK BERBASIS ASSET BASED COMMUNITIES DEVELOPMENT: PENGALAMAN TIM PENGABDIAN KEPADA MASYARAKAT - Eksely, Sarah Priskila; Susanto, Adri; Handriani, Yuli; Bumen, Eko Julianto Krismanuel R.; Sanasintani, Sanasintani; Munte, Alfonso (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
This research paper serves as a forum for community service, with the objective of benefiting the State Vocational High School 2 Palangka Raya. At the same time, it strives to advance knowledge empowerment in Christian religious education. The beneficiaries of this program are educational actors, including teachers, principals, and students, who participate in the construction of spiritual and competent relationships among community engagement participants. The authors' methodology is an Asset-Based Community Development (ABCD) approach that prioritizes the resources available at the school for the development of PAK learning media. The results obtained by the authors during approximately three months of meeting and befriending the students provided a sustainable perspective on the issues raised by reading books relevant to the PAK themes. Furthermore, the authors identified the opportunity to be creative with school resources as a potential avenue for interdisciplinary collaboration in education at SMK Negeri 2 Palangka Raya.